2009
DOI: 10.1007/s10551-009-0305-8
|View full text |Cite
|
Sign up to set email alerts
|

“Harmonious” Norms for Global Marketing the Chinese Way

Abstract: China, law, marketing, intellectual property, advertising, World Trade Organization, harmonious society,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 15 publications
0
2
0
Order By: Relevance
“…Wang and Lin (2009) note that China currently is experiencing cultural renaissance, that is going back to the roots of Chinese culture, while creatively resisting the Western influence. However, Choukroune's (2009) analysis showed that legal reforms did not truly reflect Confucian values, while the population and marketers were positively predisposed towards implementing these values. Li et al (2009) show that governance regimes and choices influence how marketing channel behaviours (e.g.…”
Section: Contextual Factorsmentioning
confidence: 96%
“…Wang and Lin (2009) note that China currently is experiencing cultural renaissance, that is going back to the roots of Chinese culture, while creatively resisting the Western influence. However, Choukroune's (2009) analysis showed that legal reforms did not truly reflect Confucian values, while the population and marketers were positively predisposed towards implementing these values. Li et al (2009) show that governance regimes and choices influence how marketing channel behaviours (e.g.…”
Section: Contextual Factorsmentioning
confidence: 96%
“…Wang and Lin (2009) note that China currently is experiencing cultural renaissance, that is going back to the roots of Chinese culture, while creatively resisting the Western influence. However, Choukroune's (2009) analysis showed that legal reforms did not truly reflect Confucian values, while the population and marketers were positively predisposed towards implementing these values. Li et al .…”
Section: Chopsticks Marketing: General Theoretical Frameworkmentioning
confidence: 96%